Implementation And Simulation Of Dynamic Arp Inspection In Cisco Packet Tracer For Network Security - Putra, Fauzan Prasetyo Eka; Ubaidi, Ubaidi; Tamam, Alief Badrit; Efendi, Reynal Widya (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Dynamic ARP Inspection (DAI) is a security feature that helps prevent Address Resolution Protocol (ARP) spoofing attacks, which can compromise the integrity and confidentiality of data in a network. This paper presents the implementation and simulation of DAI using Cisco Packet Tracer, a network simulation tool. The goal is to show how DAI can be configured and used to improve network security by verifying ARP packets in a switched network. The implementation involved setting up a network topology with switches and end devices, configuring DHCP snooping, and enabling DAI on the switches. Simulations tested various scenarios, including normal operation, ARP spoofing attacks, and the network response to these attacks with DAI enabled. The results show that DAI effectively mitigates ARP spoofing attacks, ensuring only legitimate ARP packets are forwarded, thus protecting the network from potential security breaches. The study concludes that implementing DAI is an important step in securing networks, especially in environments with sensitive data and high security needs. This paper serves as a practical guide for network administrators looking to improve their network security posture using Cisco Packet Tracer.